Numerical study on wave-induced hydro-elastic responses of a floating raft for aquaculture. (15th November 2021) - Chu, Bei; Chen, Yiren; Zhang, Yao; Zhang, Guangming; Xiang, Xu; Zhang, Xinshu
Abstract: The paper presents the study on hydro-elastic responses of a floating raft with a mooring system in both regular and irregular waves. The floating raft consists of a number of buoys, plates and a mooring system, which are modeled by Morison type elements with proper coefficients, segmented line elements with stiffness and several mooring cables, respectively. The added mass coefficients of the buoys are computed by using the panel code WAMIT. Damping coefficients are obtained by CFD simulations of the forced surge/sway motions of a buoy with a free surface. Due to the nonlinear performance of the mooring system, the periods of maximum responses of the structure decrease as the wave height increases. For regular waves, the most of dangerous wave conditions are found in the wave periods 6 ∼ 10 s with the incident wave angles 0 ∘ ∼ 2 0 ∘ or 7 0 ∘ ∼ 9 0 ∘, while the floating raft is relatively safe for the incident wave angle being around 45°. For irregular waves, the impacts of randomness are analyzed by using different wave seeds. Most of the results are not sensitive to the randomness of the phase angles, except for the maximum mooring tensions which show noticeable fluctuations ( ∼ 15 % ). By comparing the results of the long-crested wave and short-crested wave, it is found that the predictions of the mooring tension and the responses of the floating raft are more conservative in long-crested wave than those in short-crested wave. Besides, the impacts of different frequency ranges on the time histories of the responses are discussed. The maximum structural responses are compared with the most probable maximum (MPM) values obtained by assuming Rayleigh distribution for the responses. The most vulnerable locations of the structure are analyzed based on the maximum dynamic loads on the plates of the floating raft. When the zero-crossing period exceeds 5 s, the relatively large tensions on the plates occur in the north and south sides of the floating raft. The relatively large shear force, bending moment, normal stress, torque and shear stresses on the plates always occur in the four corners of the floating raft. Highlights: The hydro-elastic responses of a new-type floating raft in regular and irregular waves are computed and the most vulnerable locations are identified. The nonlinear performance of the mooring system is evaluated and confirmed by using a simplified theoretical model. The viscous force on the buoys is computed by assigning drag coefficients, which are obtained by CFD simulations of the forced surge and sway motions of a buoy with a free surface. The extreme values observed from the time histories are compared with those predicted using standard deviation based on Rayleigh distribution.